2014
DOI: 10.1038/srep06030
|View full text |Cite
|
Sign up to set email alerts
|

Tracking and quantification of dendritic cell migration and antigen trafficking between the skin and lymph nodes

Abstract: Skin-derived dendritic cells (DCs) play a crucial role in the maintenance of immune homeostasis due to their role in antigen trafficking from the skin to the draining lymph nodes (dLNs). To quantify the spatiotemporal regulation of skin-derived DCs in vivo, we generated knock-in mice expressing the photoconvertible fluorescent protein KikGR. By exposing the skin or dLN of these mice to violet light, we were able to label and track the migration and turnover of endogenous skin-derived DCs. Langerhans cells and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
151
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(164 citation statements)
references
References 50 publications
5
151
2
1
Order By: Relevance
“…by Langerin + DCs. It is known that in the skin, Langerin + dermal DCs traffic between the skin and peripheral lymph nodes [55]. In the intestine it has not been determined whether Langerin + DCs are migratory.…”
Section: Discussionmentioning
confidence: 99%
“…by Langerin + DCs. It is known that in the skin, Langerin + dermal DCs traffic between the skin and peripheral lymph nodes [55]. In the intestine it has not been determined whether Langerin + DCs are migratory.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, failure of a population to exchange in parabiosis does not imply that cells of that population are sessile and static. For example, in the absence of inflammation, Langerhans cells remain overwhelmingly host-derived in parabiotic mice (Merad et al, 2002), although they migrate continuously and unidirectionally from the epidermis to skin-draining lymph nodes (Bajaña et al, 2012; Ohl et al, 2004; Tomura et al, 2014). Additionally, imaging studies have shown that liver-resident iNKT cells, epidermis-resident CD8 + T RM cells, and intestine-resident ILCs exhibit dynamic behavior within their respective tissues (Gebhardt et al, 2011; Geissmann et al, 2005; Mackley et al, 2015; Pearson et al, 2016; Zaid et al, 2014) but self-renew locally and are not replaced by circulating precursors (Gasteiger et al, 2015; Jiang et al, 2012; Thomas et al, 2011).…”
Section: Definition Of Tissue-resident Populationsmentioning
confidence: 99%
“…The reason for this faster turnover is unclear, but it may reflect their more invasive method to surgically expose the SDLNs (30).…”
Section: Dec-205mentioning
confidence: 99%